THEORETICAL APPROACHES TO ANALYSIS OF «MEGABANK» PROFITABILITY - S. V. Shubіna; I. V. Kramarenko; A. V. Golovashko (Фінансово-кредитна діяльність: проблеми теорії та практики)
The article focuses on theoretical and methodological approaches regarding the bank profitability analysis. The factor analysis of the economic impact of withdrawing capital on the system parameters on the example of PJSC «MEGABANK» has been offered. The study presents analysis of the research involves the ways to increase it’s efficiency PJSC «MEGABANK» performance and it’s profitability. Taking into account for the banking institution such an index as profitability, improvement the ways of research based on theoretical and methodological approaches of the well known home and foreign scholars is proposed (on the example of PJSC «MEGABANK») expanding the bank’s effectiveness analysis based on the use of factor model of economic return on capital. The factors system proposed it’s to indicate the most important economic impact concerning the formation of return on capital as an important indicator of the banking institution profitability, namely: the economic return on capital, profitability, profit margin, return on assets, multiplier of capital.